2017
DOI: 10.11648/j.eco.20170606.11
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tax Revenue in Ethiopia

Abstract: Abstract:Fiscal deficit is the core issue of most of the developing countries over the past several decades. The reason behind the large increase in fiscal imbalance is the rapid expansion in expenditure and low revenue collection. Hence, efficient tax system is crucial for these countries. Since Ethiopian is one among developing countries, pattern of tax revenues and economic growth across country has become a significant concern. Due to aforementioned deficiencies, Ethiopia struggles with budget deficits for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 5 publications
9
11
1
2
Order By: Relevance
“…The variables FDI share revealed negative coefficient of nearly of 0.23% and significantly; this is an unexpected result for developing country like Tanzania. However, these findings also aligned with previous studies Castro and Camarillo [1], Gorbachev et al [14]. During economic reform and trade liberalisation in 1990's, foreign direct investment policy structured with an excessive tax exemption for short and long-term which benefit foreign investors greatly for paying little or no tax.…”
Section: Discussion Of Tax Performancesupporting
confidence: 90%
See 3 more Smart Citations
“…The variables FDI share revealed negative coefficient of nearly of 0.23% and significantly; this is an unexpected result for developing country like Tanzania. However, these findings also aligned with previous studies Castro and Camarillo [1], Gorbachev et al [14]. During economic reform and trade liberalisation in 1990's, foreign direct investment policy structured with an excessive tax exemption for short and long-term which benefit foreign investors greatly for paying little or no tax.…”
Section: Discussion Of Tax Performancesupporting
confidence: 90%
“…Results in manufacturing share were expected and aligned with previous studies, Chaudhry and Munir [4], Castro and Camarillo (2014) [1], Gobachev et al [14] who found manufacturing share has a positive effect with tax performance. The manufacturing sector is among the essential sectors in boosting economic growth that claimed to associate with an increase in tax revenue performance.…”
Section: Discussion Of Tax Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…With forty two years data in Nigeria, the research result shows that the main determinants of tax revenue are the level of change in income, rate of inflation and exchange rate [10]. Another research used time series data set for the years 1999/00 to 2015/16 and the results find that in constant condition of other factors, a 1% increase in real GDP per capita income results in approximately raise in tax revenue percentage of GDP by 0.20 percent [11]. This means that GDP per capita income has a positive and significant effect on tax revenue.…”
Section: Literature Reviewsmentioning
confidence: 99%